Modeling mercury concentrations in northern pikes and walleyes from frequently fishes lakes of Abitibi-Témiscamingue (Québec, Canada): a GIS approach - Beaulne, Jean-Sébastien; Lucotte, Marc; Paquet, Serge; Canuel, René (2012)
Using readily available geospatial data and statistical analyses we constructed models to predict mercury concentrations in northern pikes (Esox lucius) and walleyes (Stizostedion vitreum) in lakes frequently used by sport fishers, urban anglers and subsistance fishers in the Abitibi-Témiscamingue region (Canada). Mercury concentrations in northern pikes were predicted with 74% accuracy using three variables: lake order, fraction of the lake watershed with gentle to moderate slopes (steepness 2%–6%) and the fraction of the watershed with mature forest cover. To construct the walleye model, we divided lakes into 3 categories: (1) lakes with mines or mine tailings located less than 1 km away from the shore; (2) lakes located on the Lake Ojibway-Barlow clay plain; and (3) lakes outside the clay plain. For watersheds without mines, walleye Hg concentrations were predicted with over 77% accuracy using the fraction of wetlands in the watershed.